Simultaneous estimation of risk and time preferences among small-scale cattle farmers in West Africa - Sabine Liebenehm; Hermann Waibel (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2012)
This study investigates risk and time preferences of small-holder cattle farmers in West Africa. We apply a discounted utility model and jointly estimate a prospect theory-based utility function and a quasi-hyperbolic discounting function using a maximum likelihood method. Results show that West African farmers are less loss-averse and are more patient than suggested by comparable studies in Asian developing countries. The main factors influencing farmers' risk and time preferences are cattle herd size and net revenue from sales of cattle products.
Keywords: D81; C61; C93; 330; experiments; prospect theory; risk preference; time preference; West Africa